Book review: Unity, Division and the Religious Mainstream in Sweden - Klingenberg, Maria (2022)
Book Review of Erika Willander: Unity, Division and the Religious Mainstream in Sweden. Palgrave Studies in Lived Religion and Societal Challenges, Cham: Palgrave Macmillan, 2020, 137 pp.
Keywords: Rezension